STRENGTHENING PANCASILA EDUCATION THROUGH TEACHER CAPACITY AND CONTEXTUAL CURRICULUM ENACTMENT IN A REMOTE SCHOOL - Kirie Natalia Seleky; Fatimah Sialana; Lisye Salamor (EDUCATIONE, 2026)
Improving Pancasila Education in geographically and infrastructurally constrained schools requires alignment between teacher capacity, curriculum interpretation, school leadership, and locally feasible resources. This article presents a secondary qualitative reanalysis of an archived single-school fieldwork record from SMP Negeri 02 Fena Fafan, South Buru, Indonesia. The archive contains dated observation summaries, interview excerpts from school leaders, teachers, and Grade VII-IX students, and references to school documents collected in July 2025; however, the exact participant total, raw recordings, full instruments, and systematic student-outcome measures were not available. A hybrid thematic synthesis combined inductive coding with sensitizing concepts drawn from curriculum-enactment, instructional-leadership, professional-learning, culturally relevant pedagogy, and civic-education scholarship. The archived evidence documents uneven subject-matter mastery, lecture and note-taking practices, limited contextual materials, incomplete Merdeka Curriculum understanding, and restricted digital access. It also documents enabling practices, including supervision, peer knowledge sharing, selective use of Buru language, parent-school communication, discussion, group work, video, and shared-device learning. The analysis proposes, rather than tests, a framework in which principal-led curriculum co-design links professional capacity to contextual enactment, while local-language scaffolding and low-bandwidth pedagogy operate as context-specific enabling conditions. The study offers analytically transferable propositions for similar remote-school contexts, but no causal or statistical generalization is claimed. Future multisite research should verify the framework with complete sampling, ethics, instrument, and student-outcome documentation.